2008
DOI: 10.1038/ejcn.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

Components of variation in serum carotenoid concentrations: the Polyp Prevention Trial

Abstract: Objectives: The intra-and interindividual variations and season and center effects were estimated from a series of serum carotenoid concentrations in the Polyp Prevention Trial (PPT) participants. Subjects/Methods: Fasting blood was collected annually for 4 years in all 1905 participants, and a subcohort of 901 participants were selected within each (of eight) center(s), by gender and dietary arm of the study, for measurement of five major carotenoid peaks. Using variance of component methods, the variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Various explanations for this lack of response in plasma b-carotene concentration are possible. First, the change in b-carotene intake may be too small to be reflected in a significant change in plasma b-carotene concentration, possibly because of the high intra-and interindividual variations in both the intake and plasma concentration of b-carotene (55). In addition, in intervention studies where significant responses have been observed, increases in b-carotene intake were greater (31,33), and although it would be expected that such an increase would increase concentration, it may not because of variations in the bioavailability of b-carotene from different diets (34).…”
Section: Discussionmentioning
confidence: 98%
“…Various explanations for this lack of response in plasma b-carotene concentration are possible. First, the change in b-carotene intake may be too small to be reflected in a significant change in plasma b-carotene concentration, possibly because of the high intra-and interindividual variations in both the intake and plasma concentration of b-carotene (55). In addition, in intervention studies where significant responses have been observed, increases in b-carotene intake were greater (31,33), and although it would be expected that such an increase would increase concentration, it may not because of variations in the bioavailability of b-carotene from different diets (34).…”
Section: Discussionmentioning
confidence: 98%
“…Thirdly, the study was not powered to test for interaction among the micronutrients. Fourthly, certain micronutrients with limited circulating half-lives and are more prone to intra-individual variability of serum concentration 67,68 , potentially attenuating the observed association between micronutrient status and TB risk. However, serial pre-ART blood collection to account for such variability was not feasible in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-individual variation in serum carotenoids is generally large and stem from many factors 5 . In the Healthy Eating Study from which colon biopsies were obtained for the present study, the coefficient of variation for total serum carotenoids was about 65% 6 .…”
Section: Introductionmentioning
confidence: 99%